Praktik Thrifting Di Tinjau Dari Hukum Ekonomi Syariah (Studi Kasus Di Kota Banjarbaru) - Al Adawiyah DND, Pp Rabiah; Hafidzi, Anwar; M. Hanafiah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract The practice of thrifting, which is the activity of buying or shopping for used goods, especially clothes, has become a popular social phenomenon among Indonesian people, especially the younger generation. However, this practice has also caused controversy and legal problems, especially related to the import of used clothing from abroad which is prohibited by the government. This study aims to examine the practice of thrifting in Banjarbaru City, South Kalimantan, from the perspective of sharia economic law, which is a law that regulates human economic activities based on Islamic teachings. The approach taken in this study uses a qualitative descriptive approach. And in this study will describe the practice of buying and selling used clothes in Banjarbaru City then connected with theory according to sharia economic law. The results showed that the practice of thrifting in Banjarbaru City is still in a legal gray area, because there are no specific rules governing it. The practice of thrifting in Banjarbaru City is also not fully in accordance with the principles of sharia economic law, but in transactions carried out by both parties, harmony in buying and selling is carried out in accordance with Sharia. And the goods used as the object of the transaction have been declared to be able to be sold and received by the buyer with actual conditions. The practice of thrifting in Banjarbaru City does not cause gaps for other clothing business actors, because the opening of this thrifting clothing sales stall is only open for approximately ten days a month. With this relatively short time, other clothing business actors should not feel that they will be rivaled or feel that there are indications of danger in thrifting practices in the city of Banjarbaru. However, this study recommends the Banjarbaru city government, to formulate regulations regulating thrifting practices, as a legal basis for thrifting business actors by considering legal, economic, social, cultural, and environmental aspects, as well as the principles of sharia economic law for thrifting business actors in Banjarbaru city. Keywords:  thrifting, used clothes, sharia economic law, Banjarbaru City   Abstrak Praktik thrifting, yaitu kegiatan membeli atau berbelanja barang bekas, terutama pakaian, telah menjadi fenomena sosial yang populer di kalangan masyarakat Indonesia, khususnya generasi muda. Namun, praktik ini juga menimbulkan kontroversi dan permasalahan hukum, terutama terkait dengan impor pakaian bekas dari luar negeri yang dilarang oleh pemerintah. Penelitian ini bertujuan untuk mengkaji praktik thrifting di Kota Banjarbaru, Kalimantan Selatan, dari perspektif hukum ekonomi syariah, yaitu hukum yang mengatur aktivitas ekonomi manusia berdasarkan ajaran Islam. Pendekatan yang dilakukan dalam penelitian ini menggunakan pendekatan deskriptif kualitatif. Dan dalam penelitian ini akan mendeskripsikan mengenai praktek jual beli pakaian bekas di Kota Banjarbaru kemudian dihubungkan dengan teori menurut hukum ekonomi syariah. Hasil penelitian menunjukkan bahwa praktik thrifting di Kota Banjarbaru masih berada dalam wilayah abu-abu hukum, karena belum ada aturan khusus yang mengaturnya. Praktik thrifting di Kota Banjarbaru juga tidak sepenuhnya sesuai dengan prinsip-prinsip hukum ekonomi syariah, Namun dalam transaksi yang dilakukan oleh kedua belah pihak, rukun dalam jual beli terlaksana sesuai syariat. Dan barang yang dijadikan objek transaksi telah dinyatakan bisa dijual dan diterima oleh pembeli dengan keadaan yang sebenarnya. Praktik thrifting di Kota Banjarbaru tidak menimbulkan kesenjangan bagi pelaku usaha pakaian lainnya, sebab pembukaan lapak penjualan baju thrifting ini hanya dibuka selama kurang lebih sepuluh hari dalam satu bulan. Dengan waktu yang relative singkat tersebut menjadikan pelaku usaha pakaian lain seharusnya tidak merasa akan tersaingi atau merasa ada indikasi bahaya dalam prektik thrifting di kota Banjarbaru. Walaupun demikian, penelitian ini merekomendasikan pemerintahan kota Banjarbaru, untuk menyusun peraturan yang mengatur praktik thrifting, sebagai landasan hukum bagi pelaku usaha thrifting dengan mempertimbangkan aspek-aspek hukum, ekonomi, sosial, budaya, dan lingkungan, serta prinsip-prinsip hukum ekonomi syariah bagi pelaku usaha thrifting di kota Banjarbaru.   Kata Kunci: thrifting, pakaian bekas, hukum ekonomi syariah, Kota Banjarbaru